Enhancement of Compressive Strength in Cement Admixed Bangkok Clay with Glass Fiber and Bottom Ash for Eco-Friendly Functional Road Materials - Sakol Pochalard; Chalermpon Wungsumpow; Keeratikan Piriyakul (Mechanics of Advanced Composite Structures)
This article aims at the development of new eco-friendly functional road materials, examining the optimum mixing ratio of cement, bottom ash, glass fibers, and the mechanical properties of soil-cement subbase (pavement) materials. The optimum ratio of cement, bottom ash, and glass fibers was determined for the mixing of soil-cement as eco-friendly functional road materials. This study was carried out by using the unconfined compression test. All soil-cement samples were mixed at the liquid limit of 88%, with varying glass fiber content between 0.5, 1.0, 1.5, 2.0, and 2.5% by volume respectively. The glass fiber lengths were used 3, 6, and 12 mm. The OPC content was added between 2, 4, 6, 8, and 10%, respectively by dry weight. The bottom ash content was 5, 10, 15, 20, 25 and 30% by volume respectively. All soil-cement samples were cured for 7, 14, 28, 60 and 90 days. It was found that the optimum OPC soil-cement content mixture was around 8-10% according to ACI 230.1R-09 standard which requires OPC of 10-16% and the optimum fiber content was between 1.0 and 1.5%. The best UCS result for glass fiber length was 12mm. Finally, the optimum bottom ash content was 5-10%, and the recommended curing period should exceed 28-90 days.